ChemInform Abstract: P, S Ligands for the Asymmetric Construction of Quaternary Stereocenters in Palladium‐Catalyzed Decarboxylative [4 + 2] Cycloadditions. Issue 24 (27th May 2016) - Wei, Yi; Lu, Liang‐Qiu; Li, Tian‐Ren; Feng, Bin; Wang, Qiang; Xiao, Wen‐Jing; Alper, Howard
Abstract: A hybrid P, S—ligand is designed by combining a chiral β‐amino sulfide and diphenyl phosphite.